The Essence Of Digitization, Causes Of Origin, Conditions And Levels (Texas Journal of Multidisciplinary Studies, 2024)
In this article, the importance of digital technologies in society is increasing. The issues of their widespread introduction and development of the digital economy have become a serious vital issue for every state in modern times, and the digital economy has been described in detail about the development of digital computer technologies in the field of providing online services, making electronic payments, internet trading and other types of services